Seven Bardic poems to the Meic Dhiarmada of Magh Luirg - Hoyne, Mícheál (Trinity College (Dublin, Ireland). Department of Irish and Celtic Languages, 2014)
This thesis consists of editions of seven previously unedited Bardic poems to members of the Mac Diarmada (Mac Dermot) family of Magh Luirg (Moylurg), Co. Roscommon. ‘Bardic poetry’ refers to the syllabic verse, written in a literary dialect, primarily by professional praise poets for aristocratic patrons, which flourished in Gaelic Ireland and Scotland between the thirteenth and seventeenth centuries. As a contemporary historical document, a Bardic praise-poem is an invaluable historical source for scholars of Gaelic Ireland. Using our understanding of strict Classical Irish metre and language, it is possible to detect and rectify textual corruption with a much greater degree of certainty than with prose texts, where the language was less standardised and where metre is of no assistance.
Keywords: Ph.D. Trinity College Dublin; Irish and Celtic Languages, Ph.D.